Recurrent Aggressive Angiomyxoma: A Case Report - Mashadi, Imam Rasjidi; Susanto, Christine; Wondany, Ryan Putra (Fakultas Kedokteran Universitas Brawijaya, 2016)
Aggressive angiomyxoma (AA), a rare mesenchymal tumor with high recurrence rate and infiltrative nature, most generally arises in the vulvovaginal region, perineum, and pelvis of women in reproductive age peaking from age 31 to 35 but uncommonly found on men. It appears as a slow-growing gelatinous mass, which commonly asymptomatic. Imaging studies including USG, CT scan, and MR imaging are of great importance for the diagnosis of AA on identifying the mass characteristics. This paper reports a case of a 37 year old P3A0 woman with a lump on the left side of vaginal lip for 2 weeks before admission. The lump was soft to touch and was not painful, without other accompanying symptoms. Past medical history showed the lump has recurred after being surgically removed. On physical examination, a lump was found on the left vulva with soft consistency. CT scan showed a well-circumscribed hypodense mass on left labia majora and showed post contrast wall enhancement. Fine needle aspiration biopsy was done and showed hypocellular smear with myxoid matrix and bleeding. The mass was then removed by vulvectomy procedure. Histopathological analysis of the mass shows infiltration of myxoid stroma with blood vessels consistent with aggressive angiomyxoma. In conclusion, AA is usually asymptomatic and has high tendency of recurrence. Imaging procedure is useful on identifying mass characteristics and biopsy can be done to establish AA diagnosis. Surgery is the main modality for the treatment of AA, and administration of gonadotropin-releasing hormone analogue can prevent further recurrence.Keywords: Aggressive angiomyxoma, gonadotropin-releasing hormone agonist, recurrent